New instruments for banking regulation and monetary policy after the crisis - Daniel Detzer (Intervention. European Journal of Economics and Economic Policies, 2012)
This paper analyzes two instruments - asset-based reserve requirements put forward by Thomas Palley and asset-based capital requirements proposed by Charles Goodhart and Avinash Persaud - regarding their merits in reducing excessive asset price inflation. A theoretical framework of asset pricing based on the ideas of Keynes and Minsky is developed, within which the working of the instruments is demonstrated and analyzed. It is shown that in theory both instruments are able to reduce excessive asset price inflation by reducing the amount of credit money and investment flowing from financial institutions into a booming sector. It is concluded that the effect of asset-based reserve requirements is more predictable and that those are therefore more suitable for the task.
Keywords: E12; E52; G12; G18; 330; Monetary policy; banking regulation; asset prices; bubbles; Minsky; financial instability hypothesis; asset based reserve requirements; capital require- ments; macroprudential regulation